Teaching English to EFL Students in A Culturally - Specific Context: A Comparative Case Study - Samsudin Samsudin; La Ode Rasmin; Sukarismanti Sukarismanti (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
Teaching English in particular cultural contexts requires supporting skills, such as situating teaching strategies and learning material with students’ conditions and intercultural sensitivity. This study explores how the lecturers teach English to EFL Students in a culturally specific context. The design of this study used multiple case studies. This study's data collection uses semi-structured interviews through Zoom meetings with two English lecturers who taught English in Gorontalo and Papua. Then the data analysis used a thematic analysis. The findings of this study show that teaching English in Gorontalo and Papua needs some supporting competencies, such as intercultural competence (lecturers’ ability to adapt to the new culture and environment and understand how students behave, think, and interact) and pedagogical competence (lecturers’ ability in formulating, adapting, and negotiating appropriate teaching method and learning material with students need). The results of this study expand the discourse surrounding the instruction of English as a foreign language within culturally-specific contexts, highlighting the significance of multilingual education in the Indonesian context. Therefore, this study implies that lecturers who teach in a culturally different context should have those competencies so they are not culture shock.